Lifetime optimisation for linear wireless sensor networks under retransmission. (2016) - Li, Ruiying; Liao, Haitao; Liu, Xiaoxi; Huang, Ning
The lifetime of wireless sensor networks (WSN) is strongly affected by the energy consumption, which is partly attributed to retransmission. In this paper, the energy consumption of a linear WSN is analysed based on basic energy consumption models and a retransmission model. Optimisation models are proposed with the objective of maximising WSN lifetime under the coverage and success transmission rate constraints. In particular, for traditional uniform and non-uniform sensor deployment problems without considering the sleep/wakeup mechanism, the number of sensors and their distances are optimised. Moreover, for a linear WSN with a sleep/wakeup mechanism, a sensor deployment scheme is developed by optimally assigning sensors to fixed locations. The genetic algorithm and the generalised reduced gradient method are applied to solve these problems. Our case studies illustrate that the lifetime of WSN with and without retransmission are different, and it is important to consider retransmission in WSN lifetime optimisation.